Pengembangan Media Berbasis Mind map untuk Meningkatkan Pemahaman Siswa pada Pelajaran Teknik Pengolahan Video - Cobena, Desy Yanty; Maryono, Dwi; Basori, Basori (Department of Electronic and Informatic Engineering Education, Faculty of Engineering, UNY, 2019)
Learning achievement determined by acceptance of students' understanding of learning material. Therefore, a media that makes it easy for students to receive learning materials is needed. This research aims to create an interactive learning media with mind map concept in Video Processing subject. Method used in this research was research and development with 5 steps, (1) problem and potency analysis, (2) data collection, (3) product design, (4) design validation, and (5) design improvement. Media's advisability, which had developed, in percentage are 89% from media expert, 92% from material expert, 85% by users (limited) and 87% from users (expanded). It can be concluded that the design of learning media is